Landslide hazards in eastern Himalayas (Journal of Nepal Geological Society, 2000)
The Himalayas, with extreme variations in relief, are characterised by very steep slopes, harsh (i.e. cold and humid) climate and a dynamic geotectonic setting. These characteristics appear responsible for widespread slope failures and mass movements, which are often accentuated by various human activities. The importance and severity of landslide phenomenon was not recognised until recently because of sparse habitation, remoteness of its occurrence, and limited sphere of influence of the individual slides. During the last few decades, increasing developmental activities, such as unplanned urbanization, communication, dam construction, deforestation, and agriculture, have substantially affected the geo-environment and aggravated the landslide hazard in the eastern Himalayas.Three sample areas: i) along the National Highway 31 A (the East Sikkim District), ii) in the area of the Rarnmarn Hydroelectric Project Stage II (the Darjeeling District), and iii) in the Kalimpong Municipal area (the Darjeeling District), all within the inner tectonic belt of the Lesser Himalaya, were investigated for preparing LHZ maps on 1:25,000 scale. Landslide hazard evaluation factors (LHEF) were rated for each of the major causative factors, namely lithology, structure, slope morphometry, relative relief, land use, and drainage density, and summed up to obtain the total estimated hazard (TEHD) values for each slope facet. The TEHD values from 0 to 10 were classified into live zones of increasing relative hazard.